Implementasi Projek Pengelolaan Sampah Untuk Menumbuhkan Nilai Profil Pelajar Pancasila pada Peserta Didik SPS TP Kutilang Kec Cicurug Kab.Sukabumi - Ekawati, Lilik (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The character of caring for the environment is an attitude and action that always tries to prevent damage to the environment, and develops efforts to repair the damage to nature that has already occurred. One of the causes of environmental damage is waste. Both organic waste and inorganic waste. Garbage in theschool environment can cause pain and discomfort during learning. Therefore, teachers and school members need to prohibit and exemplify the attitude of caring for the environment through the processing of organic and inorganic waste. By utilizing the existing waste in the school environment, it is processed into goods that are useful and have high selling value. Moreover, inorganic waste needs proper processing and does not become waste. Because inorganic waste is difficult to recycle. This activity aims to foster an attitude of caring for the environment, use and processing of waste, and increase student creativity. This study uses a qualitative descriptive method, the results of this study are in the form of words and pictures. The results of this project activity are very influential in the school environment. Starting from students who dispose of trash in its place, can make various handicrafts from used goods and do not need pesticide fertilizers to help fertilize plants because organic fertilizers are already made. All waste is processed and utilized as best as possible, to create a clean, healthy, and comfortable school environment for learning.